WAYS OF DEVELOPING THE COUNTRY'S FOREIGN TRADE ACTIVITY AND ENSURING ECONOMIC SECURITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article deals with the problems of the empact of economic security to the stable development, current issues of alternative transport corridors of Uzbekistan to exit to the international sea ports. The article deals with the issues of ensuring the foreign economic security of Uzbekistan as an integral element of security. Foreign economic security is the main condition for ensuring the stable development of the national economy. Particular attention is paid to the analysis of foreign trade turnover, as well as measures to prevent threats to economic security.